Peran Pelayanan Gembala Terhadap Pertumbuhan Rohani Pemuda di Gereja JKI Injil Kerajaan Satelit Majapahit Semarang - Sudjono Sudjono; Stephanus Karnadhi; Fibry Jati Nugroho (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Spiritual growth of Youth is the process of growing in size or growing in the spirituality and context of Christianity. Spiritual growth involves trying to guide individuals who do not yet have a personal attachment to Jesus Christ toward a connection with Him, so that they can become part of God's responsible community [Latif Helen Farida, "The Influence of Teaching and Fellowship on the Spiritual Growth of Children and Adolescents," Christian Theology and Ministry (2017), 120.]. Rotto Marinus, means that spiritual growth is to provide teaching in the truth of God's word which is sown through teaching and fellowship. Therefore, in the context of pastoral ministry, a pastor of the congregation needs to teach the truth of God's word to Youth members. The pastor of the congregation plays a role in encouraging all members of the Youth to increase their spiritual growth. Good spiritual growth is greatly appreciated by Christ Jesus through His words. This study aims to explain the role of pastoral ministry on the spiritual growth of youth in the Church of the Indonesia Christian Church, Gospel of the Majapahit Satellite Kingdom, Semarang. To answer the problems and objectives of the research, qualitative research methods are used by applying data collection. The result of the research to be achieved is that the pastor of the church as a spiritual leader who plays an intense role in order to be able to increase the spiritual growth of youth well according to the teachings of Jesus in His word.